(untitled) (Journal of the College of Basic Education, 2023)
Quirk (1969) has remarked that a man’s style is as specific as his fingerprints. Stylistic analysis can in fact settle many knotty problems in ltterature. A Writer’s use of language, if studied carefully , can reveal his aesthetic personality , his deep – laid philosophy and world – view , the way he looks at the world , perhaps far more accurately than any study of his background and the literary movement he subscribes to . In fact , the question of the nature of stylistics , and its position among the various disciplines, its scope and its limits have aroused considerable discussion. The term "stylistics" can apply to various kinds of linguistic analysis. Anyhow, stylistics, which is, in general, incorporated within the terminology of linguistics, has not won the satisfaction of some linguists. therefore, they began to coin some other new terms . Thus, this research is intended to present discussion of the scope of stylistics, stylistic analysis, and stylistics as a middle ground between linguistics and literary criticism. In general, it is divided into three parts each to cover a certain aspect of the subject .the first part is a review of the definition of stylistics, its function, and its aims. The second part is concerned with stylistic analysis and kinds of stylistic studies. Whereas, the third part of this research discusses the role of stylistics as a contact between linguistics and literary criticism.